2019
DOI: 10.1017/s1751731119001745
|View full text |Cite
|
Sign up to set email alerts
|

Review: Impact of food, gut–brain signals and metabolic status on brain activity in the pig model: 10 years of nutrition research using in vivo brain imaging

Abstract: The purpose of this review is to offer a panorama on 10 years of nutrition research using in vivo brain imaging in the pig model. First, we will review some work describing the brain responses to food signals, including basic tastants such as sweet and bitter at both oral and visceral levels, as well as conditioned preferred and aversive flavours. Second, we will have a look at the impact of weight gain and obesity on brain metabolism and functional responses, drawing the parallel with obese human patients. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 103 publications
(122 reference statements)
0
22
0
1
Order By: Relevance
“…Moreover, digital stereotaxic atlases are available and many classical human imaging techniques have been implemented in the pig model [17,18]. Thus, pig is a particularly relevant model to study brain responses using in vivo imaging [17,19]. We have notably been working on the development of adequate techniques to discriminate the brain responses to gustatory [20] and olfactory stimulations [21] through fMRI in this model [17,19].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, digital stereotaxic atlases are available and many classical human imaging techniques have been implemented in the pig model [17,18]. Thus, pig is a particularly relevant model to study brain responses using in vivo imaging [17,19]. We have notably been working on the development of adequate techniques to discriminate the brain responses to gustatory [20] and olfactory stimulations [21] through fMRI in this model [17,19].…”
Section: Introductionmentioning
confidence: 99%
“…fMRI is a non-invasive neuroimaging approach that can be used to investigate sensory, cognitive, and hedonic integration of exteroceptive or interoceptive stimuli in healthy or pathological subjects. Our laboratory has a world-recognized 10-year experience in using functional brain imaging in the pig model for nutritional and translational research [31]. Notably, we previously described, using fMRI or nuclear brain imaging, the pig brain responses to sucrose stimulation or palatable food flavors [95,96] and demonstrated that obese minipigs have similar brain anomalies as obese humans [30].…”
Section: Toward a Preclinical Study In The Diet-induced Obese Minipigmentioning
confidence: 99%
“…All the technologies required for this proof of concept and identification of the best EA acupoints combination have already been implemented in the minipig model [31]. As stated before, this encompasses metabolic, physiological, and behavioral explorations, as well as minimally invasive neurobiological measures of the vagus nerve activity [97] and brain responses to various stimuli via fMRI [96,98].…”
Section: Toward a Preclinical Study In The Diet-induced Obese Minipigmentioning
confidence: 99%
See 1 more Smart Citation
“…Olfactory and gustatory stimulations have already been widely investigated in the pig and minipig models. Roura and Fu (2017) and Val-Laillet (2018) have recently provided complete reviews on this topic and the scope of the methodologies used for this purpose come from ethology ( Clouard et al, 2012a , c ; Clouard and Val-Laillet, 2014 ) to electrophysiology ( Danilova et al, 1999 ) and nuclear imaging, such as single photon emission computed tomography (SPECT) or positron emission tomography (PET; Clouard et al, 2012a , 2014b ; Val-Laillet et al, 2015 ; Val-Laillet, 2018 ). These approaches provide either information about a long-term integration of the stimulation, i.e., behavior or nuclear imaging, or a direct but local impact, i.e., electrophysiology.…”
Section: Introductionmentioning
confidence: 99%